Anxiety and Depression in Ireland during COVID-19 – a narrative review - V. Sathyanarayanan; D. Shahwar; M. Azeem (European Psychiatry, 2022)
Introduction Ireland has been one of the worst affected countries affected by COVID-19 in Europe. Many primary studies from Ireland have documented prevalence of anxiety and depressive disorders during the pandemic and their correlates.